2021
DOI: 10.1002/anie.202104592
|View full text |Cite
|
Sign up to set email alerts
|

Anion⋅⋅⋅Anion Coinage Bonds: The Case of Tetrachloridoaurate

Abstract: Interactions in crystalline tetrachloridoaurates of acetylcholine and dimethylpropiothetine are characterized by Au⋅⋅⋅Cl and Au⋅⋅⋅O short contacts. The former interactions assemble the AuCl4− units into supramolecular anionic polymers, while the latter interactions append the acetylcholine and propiothetine units to the polymer. The distorted octahedral geometry of the bonding pattern around the gold center is rationalized on the basis of the anisotropic distribution of the electron density, which enables gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 49 publications
(63 reference statements)
1
48
0
Order By: Relevance
“…Furthermore, each group of the p-block possesses its own terminology, which are aerogen or noble gas bonding (NgB, group 18) [12], pnictogen bonding (PnB, group 15), [18,19] tetrel bonding (TtB, group 14) [20], and triel bonding (TrB, group 13) [7]. In addition, matere bonding (MaB, group 7) [21], osme bonding (OmB, group 8) [22], spodium bonding (SpB, group 12) [23], and regium or coinage bonding (CiB, group 11) have been used to refer to NCIs in which elements from groups 10 and 11 act as Lewis acids and to differentiate these types of interactions from classical coordination bonds [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, each group of the p-block possesses its own terminology, which are aerogen or noble gas bonding (NgB, group 18) [12], pnictogen bonding (PnB, group 15), [18,19] tetrel bonding (TtB, group 14) [20], and triel bonding (TrB, group 13) [7]. In addition, matere bonding (MaB, group 7) [21], osme bonding (OmB, group 8) [22], spodium bonding (SpB, group 12) [23], and regium or coinage bonding (CiB, group 11) have been used to refer to NCIs in which elements from groups 10 and 11 act as Lewis acids and to differentiate these types of interactions from classical coordination bonds [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] This is not the only bond, as there appear to also be a number of NHÁ Á ÁCl H-bonds, and several that link the central Pd with an NH group on a counterion, but most have a smaller r BCP . A comparison can be drawn with the tetrachloridoaurate(III)-based complex, 42 which had smaller densities in the range of 0.006-0.011 au. Complementary to QTAIM is the NCI protocol which depicts noncovalent interactions via a color scheme.…”
Section: àmentioning
confidence: 99%
“…A Cl atom of one unit lies directly above the Pd of its neighbor, with a R(PdÁ Á ÁCl) distance of 3.181 Å, quite a bit smaller than the sum of their vdW radii of 3.97 Å. 41 The normalized contact (Nc) 42 ratio between the actual distance and this vdW sum is 0.80, significantly shorter than the AuÁ Á ÁCl and AuÁ Á ÁO coinage bond contacts of 0.88 and 0.95, respectively, in an analogous tetrachloridoaurate(III) crystal. 42 The molecular electrostatic potential (MEP) surrounding each monomer is displayed in Fig.…”
mentioning
confidence: 99%
“…The bulk of these findings pertain to halogen bonds 36–46 but there are recent studies beginning to emerge that indicate similar sorts of attractive anion–anion interactions apply to pnicogen bonds 47 and to those between systems such as AuCl 4 − pairs. 48 Our own group has been actively engaged in studies to test the boundaries of these ideas. Calculations have indicated that anions that can engage in complexes with one another include MCl 3 − where M refers to Group 2 49 and Group 12 (so-called spodium bonds), 50–52 pnicogen bonds of the ZCl 4 − type, 53 triel bonds involving TrCl 4 − , 54 and aerogen bonds with AeX 5 − .…”
Section: Introductionmentioning
confidence: 99%